Biosorpsi Ion Logam Tembaga (Cu2+) Pada Biosorben Rumput Laut Coklat (Padina australis) - Bijang, Catherina M.; Latupeirissa, Jolantje; Ratuhanrasa, Marike (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2018)
The research on the biosorption of Cu2+ metal ions in brown seaweed biosorbent (Padina australis) has been done. This study aims to determine moisture content, ash content, biomass content, pH and optimum contact time of Cu2+ metal ions absorption pH and optimum contact time of Cu2+ metal ions absorption. The method used is batch method. The adsorption result of Cu2+ metal ions was analyzed by using atomic absorption spectrophotometer (AAS). The results showed that the optimum pH was 7 with 99.8308 % absorption ability of biosorbent and the optimum contact time was 5 hours with 99.5570 % biosorbent absorbency.